Global Strategy for the Health of Women, Children, and Adolescents: 2016-2030. Issue 3 (May 2016) - Callister, Lynn Clark
Abstract : Global strategies associated with the new sustainable development goals provide clear direction for the future. All women and children world-wide deserve a healthy life where they have the ability to succeed and be all that they can be. The goals for maternal-child health are achievable with continued and collective effort of those with more resources.